LANGUAGE IS A CRITERIA OF POWER, INTEGRITY AND UNITY OF THE PEOPLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the status of the Uzbek language as the state language, its importance, the role of the language in society, the work done in the field of the native language during the years of independence and future tasks; Attitudes are expressed towards the names used in the Uzbek language.